Role of bacteria in dieback disease of Dalbergia sissoo roxb (Bangladesh Journal of Botany, 2013)
The possible role of bacteria as pathogens in dieback affected Dalbergia sissoo Roxb. (sissoo) trees in Bangladesh has been investigated. Among the high diversity of bacterial genera detected by 16S rDNA sequences, several plant pathogenic Pseudomonas strains were identified and classified by AFLP analysis. Three isolates produced significant symptoms on D. sissoo seedlings after mechanical inoculation in vivo, suggesting that Pseudomonas should be considered as a potential cause for the dieback disease. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15710 Bangladesh J. Bot. 42(1): 1-16, 2013 (June)